Using inverse functions, it is found that the value of [tex]g^{-1}(g(-2))[/tex] is equals to:
A) -2.
To find the inverse of a function y = f(x), we exchange x and y, and isolate y.
In this problem, the function is:
g(x) = 3x - 4.
That is:
y = 3x - 4.
Exchanging x and y and isolating y:
x = 3y - 4
3y = x + 4
[tex]y = \frac{x + 4}{3}[/tex]
[tex]g^{-1}(x) = \frac{x + 4}{3}[/tex]
Then:
Hence option A is correct.
More can be learned about inverse functions at https://brainly.com/question/8824268
#SPJ1